Journalistic approach of obesity in the Colombian press during the years 2008 - 2013 - Correa Madrid, María Camila; Carmona Garcés, Isabel Cristina; González Zapata, Laura Inés (Universidad y Salud, 2016)
Introduction: One of the functions of the mass media is to mobilize society and the political agenda around public issues such as obesity. Objective: To describe the approach given to obesity in two Colombian newspapers during the years 2008-2013. Materials and methods: A cross-sectional study was conducted were 163 news were selected from two newspapers; 48 from El Espectador newspaper and 115 from El Colombiano. First a deductive analysis of the news was performed and then a descriptive analysis using X2 tests to establish the relationship between the variables. α<0.05. SPSS v.18. Results: An increase in obesity-related news was found. The sources of information most frequently consulted to build the news were scientific-academic ones (42.3%). It was found an association between the articles dealing with the magnitude of the obesity, the strategies to confront it and when it was used a politician source (p <0.05). In the pediatric population, issues related with advertising (16.4%) and fast food (26.9%) had greater coverage (p <0.05). Conclusion: The mass media news related with obesity increased in Colombia, at the same time the implementation of strategies for prevention and control of this disease started. This situation can foster public and political mobilization that promote new strategies that contribute to the solution of the obesity problem.